Learning Abbreviation Style of French Language Conversationon Twitter - Kursini, Nani (FKIP Universitas Lampung, 2019)
Learning Abbreviation Style of French Language Conversation on Twitter. Objectives: This study aims to identify the process of formation of abbreviation, the causes of its use and its implication in French instruction. Method: This study used qualitative descriptive method, by taking utterances containing forms of abbreviation in French conversations conducted by several native speakers on Twitter from June to October 2018 as data sources. Findings: No elliptical data was found. The form of troncation which is divided into several forms of beheading, namely the beheading of one or two syllables at the end of a word, decapitation of one or two syllables at the beginning of the word, combined between troncasi and condensation and the most is decapitation by consonant or vowel disappearance. Results: The results of the study showed that the abbreviation is mainly formed by troncation, sigle, and shortening by using letters having the same sound as the real word(s). Kata kunci: Abbreviation, french language conversation, troncation. DOI: http://dx.doi.org/10.23960/jpp.v9.i2.201911